Beneficial Effects of ACC Deaminase-Producing Rhizobacteria on the Drought Stress Resistance of Coffea arabica L. - Yesenia Jasso-Arreola; J. Antonio Ibarra; Flor de Fátima Rosas-Cárdenas; Paulina Estrada-de los Santos (Plants)
Given the challenges of climate change, effective adaptation strategies for crops like coffee are crucial. This study evaluated twelve 1-aminocyclopropane-1-carboxylate deaminase-producing bacterial strains selectively isolated from the rhizosphere of Coffea arabica L. cv. Costa Rica 95 in a plantation located in Veracruz, Mexico, focusing on their potential to enhance drought resistance. The strains, representing seven genera from the Gamma-proteobacteria and Bacteroidota groups, were characterized for growth-promoting traits, including ACC deaminase activity, indole-3-acetic acid (IAA) synthesis, phosphates solubilization, siderophore production, and nitrogen fixation. Strains of the genus Pantoea exhibited higher ACC deaminase activity, phosphate solubilization, and IAA synthesis, while others, such as Sphingobacterium and Chryseobacterium, showed limited plant growth-promoting traits. A pot experiment was conducted with coffee plants subjected to either full irrigation (soil with 85% volumetric water content) or drought (soil with 55% volumetric water content) conditions, along with inoculation with the isolated strains. Plants inoculated with Pantoea sp. RCa62 demonstrated improved growth metrics and physiological traits under drought, including higher leaf area, relative water content (RWC), biomass, and root development compared to uninoculated controls. Similar results were observed with Serratia sp. RCa28 and Pantoea sp. RCa31 under full irrigation conditions. Pantoea sp. RCa62 exhibited superior root development under stress, contributing to overall plant development. Proline accumulation was significantly higher in drought-stressed, non-inoculated plants compared to those inoculated with Pantoea sp. RCa62. This research highlights the potential of Pantoea sp. RCa62 to enhance coffee plant resilience to drought and underscores the need for field application and further validation of these bioinoculants in sustainable agricultural practices.